Isolation Of Fungus Identification And Tempe Nutrition Analysis In The Traditional Market Of Bandung City - Ida Ningrumsari; Lina Herlinawati (FoodTech: Jurnal Teknologi Pangan, 2020)
Tempe is a traditional food made from fermented soybean seeds. The purpose of this study was to determine the fungus contained in tempeh by isolating and identifying the fungus and analyze the nutrients contained in it. Tempe samples were taken from traditional markets from 3 places. Samples were analyzed in the laboratory, sample analyzes were performed in duplicate. Based on the results of the study found that the fungus contained in tempe are 4 isolates of Aspergillus sp and 1 isolate of Rhizopus sp. Analysis of tempe nutrition that fulfills SNI 3144: 2009 requirements, namely tempe A, protein content 16,11%, fat 9,92% and water 33,459%, while fiber content 5,18% and ash 2,97% do not fulfill SNI 3144: 2009 requirements . Tempe B fulfills the requirements of SNI 344: 2009 for protein content 16,101%, fat 84%, water 37,75%, while ash content 3,12% and fiber 5,36% do not meet SNI 3144: 2009 requirements. Tempe C fulfills SNI 3144: 2009 requirements, namely Protein 16%, Fat 9.84% and Water 33.128%, while ash content 3.128 and fiber 5.128 do not meet SNI 3144: 2009 requirements.